PERAN PENDIDIKAN AGAMA ISLAM FORMAL DAN NON FORMAL DALAM MENINGKATKAN AKHLAKUL KARIMAH - Sandhye Aji Prasetyo (Sekolah Tinggi Islam Kendal, 2023)
Islamic religious education plays a very important role in the formation of a person's morals. And education, especially morals and morals, must be given from an early age to foster children's spiritual and physical growth, both spiritual, motoric, emotional, social and shape children's characteristics into good ones. It is not only in educational institutions that the family plays an important role in educating children, the main thing is in forming their characteristics properly and correctly.There are three forms of educational institutions currently developing in our country, namely formal, non-formal and informal. Formal educational institutions are educational institutions whose curriculum is created and managed by the government from pre-school level to university level. Then non-formal educational institutions are educational institutions whose curriculum is created and managed by the community, including Islamic boarding school or diniyah educational institutions. Meanwhile, informal education is education that is built or organized by the family and environment only for education without structure and does not require permission from the government.This article discusses the role of formal and non-formal Islamic religious education in improving morals. There are still students whose morals are not good, especially morals towards teachers. Researchers want to improve good morals towards teachers in order to gain useful knowledge and blessings. This research uses descriptive qualitative using data analysis techniques in the form of observation where the researcher takes qualitative primary data sources obtained from teachers of morals and aqidah. In this research the data source is secondary. The first research is that a student must obey the teacher by getting used to it when the teacher speaks or walks, the students bow their heads while giving respect with a bowed head gesture. To produce results such as when in class students or students must enter the class first to greet and prepare the place for the incoming teacher. The second is the teacher's guidance to students, namely using concrete story methods such as studying and giving sermons and this must also be used as an example by the teacher, so that from this method students who previously behaved badly can become good so that they can be applied in society. Third, if there are students or students who are difficult to manage, namely by using the approach of providing advice and motivation so that a student has good morals, it cannot be denied that stubborn students can occur due to internal factors such as lack of love for parents, then it will be fun for the teacher to talk to the student. Thank God, in this way students can change from bad morals to good morals..